A facile isoelectric focusing of myoglobin and hemoglobin used as markers for screening of chicken meat quality in China. Issue 20 (13th June 2019) - Saud, Shah; Li, Guoqing; Sun, Yingjie; Khan, Muhammad Idrees; Ur Rehman, Ashfaq; Uzzaman, Asad; Liu, Weiwen; Ding, Chan; Xiao, Hua; Wang, Yuxing; Cao, Chengxi
Abstract: A novel analytical protocol was developed for general quality screening of chicken meat based on IEF and protein extraction. To demonstrate the developed protocol, 24 chickens were divided into three groups; each had eight chickens. The chickens in Group 1 were slaughtered by exsanguination, Group 2 asphyxiated in water, and that in Group 3 were infected by new castle disease virus. Proteins were extracted from the meat samples by using pure water as an extractant, separated by IEF, verified by western blot, and quantified via imaging analysis. The relevant experiments demonstrated that two myoglobin (Mb) bands were detected at p I 6.8 and 7.04 for all samples of Groups 1, 2, and 3, but there were additional hemoglobin (Hb) bands at p I 7.09 and 7.13 ( P  < 0.05) for the samples of Groups 2 and 3. The results implied that Hb bands might be a potential biomarker for the screening of chicken meat quality. The RSD values of two Mb bands (p I 6.8 and 7.04) in Group 1 were respectively 4.08 and 3.63%, the ones of two Hb bands (p I 7.09 and 7.13) in Group 2 were 3.66 and 2.10%, and those in Group 3 were 2.17% and 2.77%, respectively. All the RSD values indicated high stability and reliability of the developed protocol. Additionally, the protocol had a direct readout of protein bands in IEF without staining. However, it was time‐consuming and had high cost. Even so, the relevant general method and finding have potential for screening of chicken meat quality.